Laser and Photonic Systems Integration: Emerging Innovations and Framework for Research and Education. Issue 6 (November 2013) - Nof, Shimon Y.; Cheng, Gary J.; Weiner, Andrew M.; Chen, Xin W.; Bechar, Avital; Jones, Marshall G.; Reed, Claude B.; Donmez, Alkan; Weldon, Thomas D.; Bermel, Peter; Bukkapatnam, Satish T. S.; Cheng, Changqing; et al.
Abstract The purpose of this article is to review the key emerging innovations in laser and photonics systems as well as their design and integration, focusing on challenges and opportunities for solutions of societal challenges. Developments, their significance, and frontier challenges are explained in advanced manufacturing, biomedicine and healthcare, and communication. Systems, networks, and integration issues and challenges are then discussed, and an integration framework for networking laser‐ and photonic‐based services and products is proposed. The article concludes with implications and an agenda for education, research and development, and policy needs, with a focus on human, society, science, and technology integration. © 2013 Wiley Periodicals, Inc.